Screening tuberculosis patients for diabetes mellitus in a routine program setting in Kampala, Uganda: a cross-sectional study - Nsonga, Joseph; Dongo, John Paul; Mugabe, Frank; Mutungi, Gerald; Walyomo, Richard; Oundo, Christopher; Zalwango, Sarah; Okello, Daniel; Muchuro, Simon; Dlodlo, Riitta A.; Lin, Yan (F1000Research, 2019)
Uganda is located in East Africa and is among the countries with the lowest income globally. The ten health centres in this project serve populations in the under-privileged communities of Kampala. The objective of the study was to implement diabetes mellitus (DM) screening among tuberculosis (TB) patients in a routine program setting with limited resources and high human immunodeficiency virus (HIV) prevalence. Methods: A descriptive cross-sectional observational study was conducted in ten health centres in Kampala, Uganda. As part of a project to implement DM screening in a routine setting, TB patients were screened for DM by trained health workers. A fasting blood glucose (FBG) value ≥7.0mmol/l was considered to indicate DM. For this study, aggregate data was collected and analysed using SPSS for Windows, version 13.0. Results: Among 4,590 TB patients registered, 4,016 (88.0%) were screened with random blood glucose (RBG). Of those with RBG ≥6.1mmol/l, 1,093 (83.3%) were screened with FBG. In total, 92 (2.3%) patients were diagnosed with DM and 66 (71.8%) of them were newly diagnosed. The proportion of TB patients screened with FBG in the health centres varied from 58.2% to 100%. The proportion of patients screened with FBG and the prevalence of DM were significantly higher in private health centres compared with public health centres. The health centres in peri-urban areas screened more patients with RBG than those in urban areas. Health centres without DM services screened a larger number of patients with RBG and FBG than those with DM services. Conclusions: It appears feasible to implement screening TB patients for DM in routine program settings with limited resources and high HIV prevalence. Its introduction requires close collaboration between TB and DM services. The challenges identified need government attention and certain institutional and service-related factors need to be better managed at times.
Keywords: Tuberculosis; Diabetes Mellitus; Screening; Uganda